ANALISA PRODUKTIVITAS DAN BIAYA OPERASIONAL ALAT BERAT PADA PROYEK PEMBANGUNAN STREET-RACE CIRCUIT MANDALIKA - HASYIM, HASYIM; WARKA, I GEDE PUTU; ARIATI, CAHYA PURI (Universitas Mahasaraswati Mataram, 2021)
The Mandalika circuit project is a large-scale construction project built in the Mandalika Special Economic Zone (SEZ), Central Lombok, West Nusa Tenggara (NTB). The 4.31 kilometer racetrack will have 19 bends, so it requires heavy equipment to improve the quality production and increase project efficiency. The analysis conducted to obtain the hourly productivity, operating cost, income and profit of excavators, dump trucks, motor grader, vibrator roller, and water tanker used in the worksite of Mandalika circuit. The hourly productivity for structural cut with a depth of 2 to 4 meter of excavator is 17.778 m3/h and dump truck 11.755 m3/h. The excavator production for stockpiling from excavated sources is 30.521 m3/h, dump truck 13.171 m 3/h, motor graders 1839.780 m 3 /h, vibrator roller 90.414 m 3 /h and water tankers truck 71,142 m 3/h. Motor grader production for road body preparation work is 362,222 m3/h, vibrator roller 126,851 m3/h and water tanker truck 62,250 m3/h. The hourly operating cost for the excavator is Rp. 718,048,581, motor grader Rp. 670,416,081, vibrator roller Rp. 609,423,907, and water tanker truck Rp. 380,806,081. The income and profit from the use of heavy equipment are Rp. 39,488,806,755 and Rp. 3,589,981,523.05.